Method of digital automatic design of grinding operations carried out on CNC cylindrical grinding machines - Shipulin L.V. (E3S Web of Conferences, 2023)
Based on the literature review, the problem is formulated, which consists in the absence of detailed recommendations for the design of grinding operations for CNC cylindrical grinding machines. This paper provides a solution to the problem described above using the developed method, which includes: the formation of initial data, the formation of grinding cycles, and the calculated determination of cycle parameters.